17 Delay in transfer of stemi patients from district hospital to ppci centre: impact on call-to-balloon time and mortality. (27th November 2017) - Ghani, S; Keeble, T; Kelly, P; Kabir, A; Sayer, J; Clesham, G; Gamma, R; Tang, K; Jagathesan, R; Robinson, N; Aggarwal, R; Davies, J
Abstract : Introduction: Primary angioplasty (PPCI) is recommended reperfusion therapy for STEMI within 120 min of first medical call (FMC) or from when fibrinolysis could be delivered (150 min from FMC). Most STEMI patients are directly admitted to PPCI centre but some are referred via district general hospital (DGH) causing delay in transfer and call-to-balloon (CTB) time. We evaluated various segments of inter-hospital transfer delay for STEMI in Essex, the CTB times and in-hospital mortality. Methods: All STEMI transfers from 5 DGHs in Essex from January to June 2016 were assessed. Times were noted from patient, AE and ambulance records. Following sequential time delays were calculated: AE arrival to ECG (A), ECG to ambulance call (B), ambulance call to leaving DGH (C), and leaving DGH to arrival at PPCI centre (D). Results: 84 STEMIs transferred (20% of all STEMIs; 74% male; mean age 67); 50% self-presented to AE; 73% underwent PCI. The median time delays (A, B, C and D) were 35 min, 41 min, 35 min, and 29 min respectively. The overall median CTB time was 139 min (120 min and 150 min targets were met in 36% and 54% respectively); door-to-balloon time was 30 min. In-hospital mortality was 3.9% for patients transferred from DGH (compared to 2.7% for direct admissions and 3% for all STEMIs). Conclusion: There are significant delays in transferring STEMI patients from DGH to PPCI centre, adversely affecting CTB time and in-hospital mortality. A collaborative effort is required to reduce delays, aiming for FMC to ambulance call time of 30 min (equivalent to door-to-needle target for fibrinolysis).